Linezolid vs glycopeptide antibiotics for the treatment of suspected methicillin-resistant Staphylococcus aureus nosocomial pneumonia: a meta-analysis of randomized controlled trials - Walkey, Allan J; O'Donnell, Max R; Wiener, Renda Soylemez (Chest, 2011)
Methicillin-resistant Staphylococcus aureus (MRSA) is an important cause of nosocomial pneumonia. Societal guidelines suggest linezolid may be the preferred treatment of MRSA nosocomial pneumonia. We investigated the efficacy of linezolid compared with glycopeptide antibiotics (vancomycin or teicoplanin) for nosocomial pneumonia. This was a systematic review and meta-analysis of English language, randomized, controlled trials comparing linezolid to glycopeptide antibiotics for suspected MRSA pneumonia in subjects > 12 years of age. A highly sensitive search of PubMed MEDLINE and Cochrane Central Register of Controlled Trials databases identified relevant studies. Eight trials encompassing 1,641 subjects met entry criteria. Linezolid was not superior to glycopeptide antibiotics for end points of clinical success (relative risk [RR] linezolid vs glycopeptide, 1.04; 95% CI, 0.97-1.11; P = .28), microbiologic success (RR, 1.13; 95% CI, 0.97-1.31; P = .12), or mortality (RR, 0.91; 95% CI, 0.69-1.18; P = .47). In addition, clinical success in the subgroup of subjects with MRSA-positive respiratory tract culture (RR, 1.23; 95% CI, 0.97-1.57; P = .09) was not significantly different from those without MRSA (RR, 0.95; 95% CI, 0.83-1.09; P = .48), P for interaction, 0.07. The risk for adverse events was not different between the two antibiotic classes (RR, 0.96; 95% CI, 0.86-1.07; P = .48). Randomized controlled trials do not support superiority of linezolid over glycopeptide antibiotics for the treatment of nosocomial pneumonia. We recommend that decisions between linezolid or glycopeptide antibiotics for empirical or MRSA-directed therapy of nosocomial pneumonia depend on local availability, antibiotic resistance patterns, preferred routes of delivery, and cost, rather than presumed differences in efficacy.